Gender Differences in Platelet GPIIb-IIIa Activation - Faraday, Nauder; Goldschmidt-Clermont, Pascal J; Bray, Paul F (Thrombosis and Haemostasis, 1997)
Gender differences in the development of thrombotic diseases have been described in numerous clinical settings. Enhanced platelet reactivity in both sexes is associated with the development of vascular thromboses. Because activation of platelet GPIIb-IIIa receptors is a central event in thrombus formation, we examined GPIIb-IIIa function in normal male and female volunteers. Using flow cytometry, we quantitated gender differences in the number of binding sites for FITC-labeled fibrinogen (FITC-FGN) and FITC-labeled PAC-1 antibody (FITC-PAC-1). Washed platelets were incubated with either FITC-FGN or FITC-PAC-1 and activated with either ADP or thrombin receptor activating peptide (TRAP) prior to cytometric acquisition of data. The dissociation constant for FITC-FGN was the same in both sexes (approx. 1.6 x 10-7M), however, the number of GPIIb-IIIa receptors per platelet capable of binding fibrinogen was significantly greater in women than men in response to 20μM ADP (16,319 ± 1871 vs 9669±1994, p = 0.02), 20μM ADP (39,951 ± 4711 vs 25,948 ± 4953, p = 0.05) and 50μM TRAP (39,236 ± 3965 vs 21,848 ± 4159, p = 0.007). Similarly, the number of GPIIb-IIIa receptors capable of binding PAC-1 in response to ADP and TRAP was 50% to 80% greater in women than men. Binding experiments using specific anti-GPIIb-IIIa monoclonal antibodies (P2 and 10E5), as well as quantitative Western blotting experiments, showed no gender difference in the total number of GPIIb-IIIa molecules expressed. Analysis of data from female subgroups demonstrated an association of GPIIb-IIIa reactivity with menstrual phase. We conclude that GPIIb-IIIa receptors on platelets from premenopausal women are more “activatable” than those on platelets from young men. Variations in the serum concentrations of estrogens and/or progestins may modulate GPIIb-IIIa function.